Complete mitochondrial genomes of three troglophile cave spiders (Mesabolivar, pholcidae). Issue 1 (2nd January 2019) - Oliveira, Renato Renison Moreira; Vasconcelos, Santelmo; Pires, Eder Soares; Pietrobon, Thadeu; Prous, Xavier; Oliveira, Guilherme
Abstract: In this study, we report the first complete mitochondrial genome of three Mesabolivar specimens found in the interior of N4E_0023 cave from Serra Norte (Carajás), Parauapebas (Brazil). The three mitogenomes contain 14, 941, 14, 845 and 14, 727 bp, and GC content of 29.41%, 31.68% and 29.34%, respectively. All three mitogenomes include 13 protein-coding genes, 17 transfer RNA (tRNA) genes, five putative transfer RNA (tRNA) genes and two ribosomal RNA (16S and 12S rRNA). We also performed a phylogenetic analysis with the concatenated coding genes from the complete mitochondrial genomes and showed that the analyzed Mesabolibar specimens clustered together in a clade, sister to the group with two Pholcus species, the other Pholcidae species with available mitogenome.